O gesto de recontar histórias: gêneros discursivos e produção escolar escrita - SANTOS, Sandoval Nonato Gomes (Universidade Estadual de Campinas, 2018)
This thesis describes how students learning to write establish dialogical relations with language when retteling written stories in a classroom event. Taking into account that discourse gemes are produced in different social activities, this study explains how students move through discourse genres that emerge in this particular event. This study has three parts. First, the concept o f discourse genre is discussed on the basis of Bakhtin's concept of discourse genres as relatively stable forms of utterance. Secondly, the elements that constitute the event "Retelling stories" are characterized considering two aspects: the role attributed to the teacher as he tells the story, suggesting - through a particular genre called "instructions to writing" - how the students can retell the story; the activity o f retelling as realized by the students, a result of the moving through the "instructions" and other genres that have been presented, such as "fairy tales" and "legends". Finally an analysis of 30 written texts is presented. These texts were written by second grade elementary school students at the Núcleo Pedagógico Integrado (NPI) - Escola de Aplicação ofthe Universidade Federal do Pará (UFPA) in 1995 and 1996. The methodological procedures were based on what has been denominated as indiciary paradigm, which permits both the apprehension of linguistic traces manifested in the texts, as well as an understanding o f how the subject/writer who retells stories is constituted. The analysis o f the data allows us to conclude that there are no sufficient arguments to delimit rigidly discourse genres. The heterogeneity that is constitutive of children's written texts may hold consequences for the theory of discourse genres, the teaching of written language, and the theory of language acquisition. Both the act of retelling and the theory that explains it can be understood as interpretative procedures.